The concept of tax in the jurisprudence of the Colombian Constitutional Court - Romero Molina, Cesar Augusto; Bernal Sánchez, Laura Victoria; Soto Contreras, Eleazar (DIXI, 2013)
This research focuses in studying whether there actually is a concept of tax in Colombia, since the currentlaws do not employ adequate techniques to give positive norms coherence so that they maintain a certainharmony to constitutionally define taxes. Jurisprudence thus defines and gives an interpretation of thisconcept that is consistent within our legal framework, since law has defined the concept of tax by means ofinconsistent expressions and with many voids, or when the use of said expressions is fragile within the textof the law.
Keywords: Constitution; constitutional court; jurisprudence; tax